FIRST RECORD OF THE BLACK-THROATED FLOWERPIERCER Diglossa brunneiventris (Thraupidae) in Ecuador - Pozo Zamora, Glenda Marisol; Guachamín-Paladines, Gino (Revista Ecuatoriana de Ornitología, 2024)
During the tenth Christmas Bird Count in Quito, Ecuador, we recorded one Black-throated Flowerpiercer Diglossa brunneiventris on 17 December 2023, at Parque Itchimbía. This represents the first record of this species in Ecuador, c. 670 km south of the nearest locality in Colombia and 680 km north from the northernmost locality in Peru. The presence of D. brunneiventris in Ecuador could be explained by several possible factors: 1) a wandering individual; 2) an over- looked, remnant population; or 3) a Black Flowerpiercer D. humeralis individual expressing ancestral genes that derived in a D. brunneiventris-like phenotype. Specific studies are necessary to elucidate the origin of this species in Ecuador. This record highlights the importance of citizen science in advancing knowledge about birds in this country.